Джаз та його адаптація в музично-культурному просторі європи першої третини XX сторіччя - Полянський В’ячеслав; Polyansky Vyacheslav (Видавництво «Код», 2025)
Резюме. Публікацію присвячено феномену джазу, питанням становлення та адаптації його в європейському музично-культурному просторі в перших десятиріччях ХХ сторіччя. Розглянуто фактори, що більшою мірою вплинули на поширення джазу в країнах Європи, сприяли популярності цієї музики. Це, перш за все, нові засоби передачі інформації, що з’явилися в результаті технічного прогресу – радіо, грамофон, кінематограф, якими джаз з великим прагматизмом скористався. Значну увагу приділено публікаціям, як в загальних музичних періодичних виданнях, так і професіональних, суто джазових журналів.

Abstract. This publication is devoted to the phenomenon of jazz, addressing the issues of its formation and adaptation within the European musical and cultural space in the first decades of the twentieth century. It examines the factors that had the greatest influence on the spread of jazz in European countries and contributed to the popularity of this music. These were, above all, the new means of disseminating information that emerged as a result of technological progress  radio, the gramophone, and cinema  which jazz made use of with great pragmatism. Considerable attention is paid to publications both in general music periodicals and in professional, exclusively jazz-oriented journals. Indeed, in the process of adapting jazz to the European musical context, new, eccentric instruments began to appear in jazz ensembles: the xylophone, the violin-saxophone, varieties of the train flute, entire sets of noise instruments: car horns, railway horns, bells, tambourines, whistles played by a drummer, saw blades, and later the theremin. the first electronic musical instrument in history, created in 1919-1920 and named after the inventor Lev Theremin. One could meet quite «exotic» compositions, by analogy with American spasm bands, which was initially perceived as a kind of symbol of «overseas exoticism», original novelty and was associated with jazz. And only at the beginning of World War II, under the influence of overseas orchestras, did Europe begin to develop its own specific instrumentation and arrangement techniques, with an orientation towards the instrumental composition of sweet swing music. And yet, the own sound portrait of European bands («sound») clearly differed from the sound of their American ancestors, and any analyst can easily see this by comparing the recordings of one and the other orchestras of those years.
Jazz and its adaptation in the musical and cultural space of europe in the first third of the 20th century
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: джаз; імпровізація; адаптація; традиції; стиль